Impact of Academic Stress on Help-Seeking Attitudes Among Nursing Students of Kathmandu District - Niraula, Sophee; Baral, Kushalata (Journal of College of Medical Sciences-Nepal, 2024)
Background Depression, anxiety and stress are treatable conditions. However, a vast majority of people avoid seeking professional help. Interventions aiming to improve help-seeking attitudes among affected individuals, particularly within academic settings, often demonstrate limited efficacy. This study explores the relationship between academic stress and help-seeking attitudes among nursing students. Methods A descriptive cross-sectional study was conducted among 300 nursing students in Kathmandu district using simple random sampling. Data were collected using the Depression Anxiety and Stress Scale (DASS21) and additional survey questions. Statistical analysis employed chi-square tests to explore relationships between variables. Results Findings indicated that 14% of respondents had mild depression, 30% moderate depression, and 8.7% severe depression. Similarly, levels of anxiety and stress were observed, with significant associations between depression and stress related to academics (p-value 0.002). Help-seeking preferences revealed that students were more inclined to seek support from friends or intimate partners. Conclusions This study highlights the prevalence of depression, anxiety, and stress among nursing students with notable associations to their academia. Importantly, the findings emphasize the need for tailored interventions to address mental health concerns and foster proactive help-seeking attitudes among students. Further research and targeted strategies are warranted to enhance the effectiveness of interventions in this context.